A PSYCHOANALYSIS ON HELENA DE NARBONS MOTIVES AS SEEN IN WILLIAM SHAKESPEARES ALLS WELL THAT ENDS WELL - Diah Astuti (Reforma : Jurnal Pendidikan dan Pembelajaran, 2016)
This study aims to describe the essential roles of motives as humans drive in reaching ones goals and purposes in life. The analysis on motives of the female character, Helena de Narbon, was portrayed psychologically in two perspectives namely the psychological factors that have become the background of Helena de Narbons insistence to get married with Bertram and the point of view from Helena de Narbon in viewing the feminine roles at that age that she has from her family valuesKeywords: Psychoanalysis, motive, motivational drive, masculine, feminine